2020
DOI: 10.1021/jacs.0c02803
|View full text |Cite
|
Sign up to set email alerts
|

A Chiral Phenanthroline Ligand with a Hydrogen-Bonding Site: Application to the Enantioselective Amination of Methylene Groups

Abstract: A silver-catalyzed amination is reported that occurs at the aliphatic C3-substituent of various quinolones and pyridones. The C−H amination reaction proceeded with high site-and enantioselectivity (14 examples, 83−97% ee). The key to its success is the use of a chiral phenanthroline ligand that is attached via an ethynyl linker to the 8-position of octahydro-1H-4,7methanoisoindol-1-one. AgPF 6 (10 mol %) served as the silver source, PhINNs as the nitrene precursor, and 1,10-phenanthroline as the coligand. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“… 256 In a very recent publication, Bach reported an enantioselective intermolecular amination using silver catalysis ( Figure 70 a). 257 This was achieved through the use of a phenanthroline ligand functionalized with the recognition unit at the C-4 position ( Figure 70 b). An achiral 1,10-phenanthroline coligand was used alongside to assist formation of a heteroleptic silver complex.…”
Section: Carbon–heteroatom Bond-forming Reactionsmentioning
confidence: 99%
“… 256 In a very recent publication, Bach reported an enantioselective intermolecular amination using silver catalysis ( Figure 70 a). 257 This was achieved through the use of a phenanthroline ligand functionalized with the recognition unit at the C-4 position ( Figure 70 b). An achiral 1,10-phenanthroline coligand was used alongside to assist formation of a heteroleptic silver complex.…”
Section: Carbon–heteroatom Bond-forming Reactionsmentioning
confidence: 99%
“…In summary,o ur study has revealed that the directing power of hydrogen bonding ligands is not only operative in defined metal complexes but also in an equilibrium scenario with reversible coordination of chiral and achiral ligands at acationic metal center. Theo bserved site-and enantioselectivity makes several heterocyclic sulfimides available which would be difficult to access in enantioselective form by known methods of asymmetric catalysis.T he suggested reaction mechanism of the nitrene transfer which had been previously proposed to occur via anitrene-silver complex with distorted trigonal bipyramidal coordination [11] has been further corroborated and offers au seful model for the design of related phenanthroline ligands with which more remote positions of ag iven substrate can be aminated. Figure 4.…”
Section: Resultsmentioning
confidence: 62%
“…Thed evelopment of chiral ligands with al actam hydrogen bonding site continues to be aresearch focus of our group. [9] Thegoal is to achieve not only an improved site-selectivity in ag iven transition-metal catalyzed reaction [10] but also to induce as ignificant enantioselectivity.I narecent contribution, [11] we prepared chiral phenanthroline ligands 1 which are based on the readily available octahydro-1H-4,7-methanoisoindol-1-one skeleton. [12] Their synthesis can be achieved by Sonogashira cross-coupling of known alkyne 2 [13] with the respective bromo-substituted phenanthroline (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations